Estudo comparativo da resistência à fratura de pré-molares superiores íntegros e restaurados com amálgama aderido - Minto, André Marcelo Peruchi; Dinelli, Welingtom [UNESP]; Nonaka, Tomio; Thomé, Luis Henrique De Camargo (Sociedade Brasileira de Pesquisa Odontológica e Faculdade de Odontologia da Universidade de São Paulo, 2002)
The purpose of this in vitro study was to determine the fracture resistance of upper premolars which had received class II preparations (conservative and extensive) and were restored with bonded amalgam, with two different adhesive systems. Seventy teeth were divided in four groups: group 1 (control), with ten sound teeth; group 2, with twenty prepared teeth (10 teeth received conservative cavities and 10, extensive cavities) restored with amalgam without any kind of liner; groups 3 and 4, similar to group 2, though with linings of glass ionomer cement (Vitrebond - 3M) (group 3) and dental adhesive (Scotchbond Multi-Purpose Plus - 3M) (group 4). The teeth were previously fixed in PVC cylinders with acrylic resin. After being restored and thermocycled, the test specimens were submitted to fracture by means of compression in an EMIC-MEM 2000 universal testing machine. After the application of the analysis of variance and complementary Tukey's test, we concluded that the utilized adhesive systems produced an increase of the fracture resistance of teeth presenting with conventional cavities; the teeth presenting with conservative cavities were more resistant in all experimental situations.

No presente estudo avaliou-se, in vitro, a resistência à fratura de pré-molares superiores preparados com cavidades de classe II compostas (conservadoras e extensas) restauradas com amálgama aderido a dois tipos diferentes de sistemas adesivos. Setenta dentes foram divididos em 4 grupos: grupo 1 ou controle com 10 dentes íntegros; grupo 2 com 20 dentes, sendo 10 cavidades conservadoras e 10 extensas restauradas com amálgama sem qualquer tipo de forramento. O grupo 3 e o grupo 4 foram compostos da mesma forma que o grupo 2, sendo que o primeiro recebeu cimento de ionômero de vidro (Vitrebond - 3M) e o segundo, adesivo dental (Scotchbond Multi-Purpose Plus - 3M), antes de serem restaurados. Os dentes haviam sido incluídos anteriormente em cilindros de PVC e fixados com resina acrílica. Após serem restaurados e termociclados, foram submetidos à fratura por força de compressão em uma máquina universal de testes EMIC-MEM 2000. Após análise de variância e aplicação do teste complementar de Tukey, concluiu-se que os sistemas adesivos utilizados condicionaram o aumento da resistência à fratura da estrutura dental nas cavidades convencionais, sendo os dentes com cavidades conservadoras mais resistentes em qualquer condição experimental.
Comparative study of the fracture resistance of sound upper premolars and upper premolars restored with bonded amalgam
Keywords: Resistance to fracture; Dental cavity preparation; Dental amalgam; Dentin-bonding agents; Bicuspid; Resistência à fratura; Preparo da cavidade dentária; Amálgama dentário; Adesivos dentinários; Bicúspide